The Effect of Alkali Soaking Time on The Deflection of Coir Fiber Composites - Lery Alfriany Salo; Dina Ramba; Fikran Fikran; Eky Setiawan S (Green Publisher Indonesia, 2026)
Natural fiber composites have the potential to serve as environmentally friendly materials; however, the quality of fiber–matrix interfacial bonding is strongly influenced by the initial treatment of the fibers. This study aimed to analyze the effect of alkali immersion time on the flexural deflection of epoxy-matrix palm fiber composites. Palm fibers were soaked in a 5% NaOH solution for varying durations of 0, 1, 3, 5, and 7 hours. The composites were fabricated with a volume fraction of 70% epoxy and 30% palm fiber and were tested for flexural deflection in accordance with ASTM D790 under a constant load of 6 kg (≈58.86 N). Each variation was tested using three replicate specimens. The results showed that flexural deflection decreased as immersion time increased, reaching a minimum at 5 hours, and then increased again at 7 hours. The highest average deflection was observed in composites without alkali treatment (5.20 mm), while the lowest deflection (4.23 mm) occurred at 5 hours of immersion, indicating improved flexural rigidity. Statistical analysis showed a coefficient of variation below 6%, indicating good data consistency. This behavior is associated with the reduction of lignin and hemicellulose content and improved fiber–matrix interfacial bonding. Overall, an alkali immersion time of 5 hours was identified as the optimal condition for improving the flexural deflection performance of palm fiber–epoxy composites.